A review of national public health strategies in selected countries - Norris, Michelle; Burke, Eimear; Comaskey, Fearghal; Connolly, Máire A.; Doyle, Yvonne; McLoughlin, Carol; McManus, Leah; Power, Valerie; Spillane, Susan; Ryan, Máirín; O’Neill, Michelle (Frontiers in Public Health, 2025)
National public health strategies play an essential role in defining a country’s vision, policy direction and approaches for ensuring the health of its population. Gaining an understanding of the public health issues which countries prioritize, and how these health issues are improved upon, may provide insights into effective methods of national public health strategy development and delivery. National public health strategies were identified for ten countries and a descriptive analysis of strategy contents and development was undertaken. All of the identified national public health strategies included an overall aim of improving health and wellbeing, and all strategy scopes extended beyond the health domain. Themes or priorities frequently identified included promoting healthy living or behaviors, the strengthening of public health, and equity or equality. Approaches to strategy implementation were considered to be prescriptive or interpretive, with prescriptive approaches including detailed implementation plans with specific actions and key performance indicators, and interpretive approaches including high-level strategic actions along with principles to support their implementation. National public health strategy development was informed by both evidence and engagement with stakeholders, including the public, experts, and representatives from governmental and non-governmental organizations at local, regional and national levels. Overall, while the information gained in this analysis assists in the development of a national public health strategy, variation observed across the included strategies indicates that consideration should be given to factors which vary from country to country. These factors include the national health profile, the political context, underpinning and associated policies, and the availability of resources.